THE DEVELOPMENT OF RELATING, EXPERIENCING, APPLYING, COOPERATING AND TRANSFERRING (REACT) MODEL TO FACILITATE CONNECTING MATHEMATICAL ABILITIES - Ismail, Khairul (Jurnal Pengajaran MIPA, 2019)
Mathematical connection is a goal in a mathematical learning, with the existence of a mathematical connection the good communication between teacher and student can occur. Based on previous research, the mathematical connections of students at school are still low. This is because so far learning has not provided opportunities for students to develop their abilities in channeling with what they have captured. One of the lessons to improve mathematical problem solving skills is Relating, Experiencing, Appliying, Cooperating and Transferring (REACT). The purpose of this study is to outline the importance of increasing the ability of mathematical connections through REACT to prepare superior generations to face MEA. Improved mathematical connection capabilities of students are expected to be able to prepare superior students who are ready to compete and be able to face the challenges of the Asean Economic Community.AbstrakKoneksi matematis merupakan tujuan dalam suatu pembelajaraan matematika, dengan adanya koneksi matematis dapat terjalinya komunikasi yang baik antara guru dan siswa. Berdasarkan penelitian terdahulu, koneksi  matematika siswa di sekolah masih rendah. Hal ini dikarenakan selama ini pembelajaran kurang memberikan kesempatan kepada siswa untuk mengembangkan kemampuannya dalam menyalurkan dengan apa yang mereka tangkap. Salah satu pembelajaran untuk meningkatkan kemampuan pemecahan masalah matematis adalah Relating, Experiencing, Appliying, Cooperating and Transferring (REACT). Tujuan penelitian ini adalah untuk menguraikan pentingnya peningkatan kemampuan koneksi matematis melalui REACT untuk mempersiapkan generasi unggul menghadapi MEA. Peningkatan kemampuan koneksi matematis siswa diharapkan mampu menyiapkan siswa unggul yang siap bersaing dan mampu dalam menghadapi tantangan Masyarakat Ekonomi Asean.Key word: Realating, experiencing, appliying,cooperating, tranfering and and mathematical conection